The Urgency of Legal Reform in Eradicating and Addressing Hate Speech - Ekaningsih, Lailasari (Yayasan Meira Visi Persada, 2024)
Hate speech is a significant issue that has been escalating with the rapid growth of social media. Hate speech involves communication actions such as provocation, incitement, or insults directed at individuals or groups based on race, skin color, gender, disability, sexual orientation, nationality, and religion. To address this issue, Indonesian law regulates such offenses through various articles in the Indonesian Penal Code (KUHP), including Articles 310, 311, 315, 317, and 318, as well as the Electronic Information and Transactions Law (UU ITE) Article 45A. Effective and consistent legal measures are necessary to curb the spread of hate speech and protect victims from its negative impacts. Awareness of legal consequences and ethical communication on social media is crucial for fostering a safer and more respectful digital environment.